2021
DOI: 10.1097/aln.0000000000004065
|View full text |Cite
|
Sign up to set email alerts
|

Opioids and Public Health: The Prescription Opioid Ecosystem and Need for Improved Management

Abstract: While U.S. opioid prescribing has decreased 38% in the past decade, opioid deaths have increased 300%. This opioid paradox is poorly recognized. Current approaches to opioid management are not working, and new approaches are needed. This article reviews the outcomes and shortcomings of recent U.S. opioid policies and strategies that focus primarily or exclusively on reducing or eliminating opioid prescribing. It introduces concepts of a prescription opioid ecosystem and opioid pool, and it discusses how the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 165 publications
(344 reference statements)
0
39
0
Order By: Relevance
“…No opioids were prescribed for patients with dental pain in the past 12-months in HDUC. Considering that about 1,800 patients received prescriptions of more than 20,000 pills of opioids annually in this clinic alone before we introduced our opioid reduction initiatives 22 , reducing the reliance on opioids for acute dental pain is particularly salient in light of a persistent OUD crisis 2,38,39 . Population-based cohort studies found that 2 - 7% of the patients receiving a dental opioid prescription would develop new and persist use of opioids within one year 9-11 .…”
Section: Discussionmentioning
confidence: 99%
“…No opioids were prescribed for patients with dental pain in the past 12-months in HDUC. Considering that about 1,800 patients received prescriptions of more than 20,000 pills of opioids annually in this clinic alone before we introduced our opioid reduction initiatives 22 , reducing the reliance on opioids for acute dental pain is particularly salient in light of a persistent OUD crisis 2,38,39 . Population-based cohort studies found that 2 - 7% of the patients receiving a dental opioid prescription would develop new and persist use of opioids within one year 9-11 .…”
Section: Discussionmentioning
confidence: 99%
“…This can be partially attributed to `big pharma´promoting the use of the World Health Organization (WHO) analgesic ladder for cancer pain for the management of types of pain that historically would be managed by simple analgesics and non-pharmacological strategies [1]. Despite the belief initially purported by the drug companies that prescribed opioids are safe, they are actually dangerous and cause death and harm by overdose and other adverse effects [2][3][4]. It is now well recognised that the global opioid crisis that started in the USA in the 1990s and directly contributed to over 100,000 deaths worldwide in 2017, originated with the aggressive marketing and subsequent misuse of prescription opioids [2,3].…”
mentioning
confidence: 99%
“…Despite the belief initially purported by the drug companies that prescribed opioids are safe, they are actually dangerous and cause death and harm by overdose and other adverse effects [2][3][4]. It is now well recognised that the global opioid crisis that started in the USA in the 1990s and directly contributed to over 100,000 deaths worldwide in 2017, originated with the aggressive marketing and subsequent misuse of prescription opioids [2,3]. The economic and societal effects of the opioid crisis on the USA economy are staggering, with an estimated 450,000 opioid-related deaths over the past two decades, and an annual financial cost to the economy of $700 billion to $1 trillion, which equates to 3.4% of the USA gross domestic product [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…That works out to roughly one opioid-related death every seven minutes. (See Kharasch et al, 2022. )…”
mentioning
confidence: 99%